The influence of ictal cutaneous allodynia on the response to occipital transcutaneous electrical stimulation in chronic migraine and chronic tension-type headache: A randomized, sham-controlled study. (April 2015) - Bono, F; Salvino, D; Mazza, MR; Curcio, M; Trimboli, M; Vescio, B; Quattrone, A
Objective: The objective of this article is to determine whether cutaneous allodynia (CA) influences the response to treatment with occipital transcutaneous electrical stimulation (OTES) in chronic migraine (CM) and chronic tension-type headache (CTTH). Methods: One hundred and sixty consecutive patients with CM or CTTH were randomized to be treated with real or sham OTES stimulation three times a day for two consecutive weeks. All patients completed the validated 12-item allodynia symptom checklist for assessing the presence and the severity of CA during headache attack. Primary end-point was change (≥50%) in number of monthly headache-free days. Results: There was a significant difference in the percentage of responders in the real OTES compared with sham OTES group ( p <0.001). Importantly, there was not a significant change of monthly headache-free days in the allodynic patients with CM and CTTH treated both with real and sham OTES, while the number of headache-free days per month was significantly reduced in the real (86%) but not in the sham group (7%) of non-allodynic patients with CTTH and CM. Conclusions: Severe CA is associated with decreased response to treatment with OTES in patients with CM and CTTH.